2020
DOI: 10.1029/2019jc015822
|View full text |Cite
|
Sign up to set email alerts
|

A New 1D/2D Coupled Modeling Approach for a Riverine‐Estuarine System Under Storm Events: Application to Delaware River Basin

Abstract: Numerical simulations of three of the most severe historical tropical cyclones to affect the Delaware River Basin (DRB) are used to evaluate a new numerical approach that is a candidate model for the inland‐coastal compound flood forecast. This study includes simulating interactions of tides/surges, freshwater streamflows, winds, and atmospheric pressure for the DRB. One‐way coupling between the hydrologic (National Water Model [NWM]) and the ocean/wave (ADvanced CIRCulation model/WAVEWATCH III [ADCIRC/WW3]) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 50 publications
1
44
0
Order By: Relevance
“…Decoupling of different shallow water processes, where hydrodynamics and ocean waves are modeled stand-alone or in a one-way fashion, introduces error in the models' outputs. Note that the necessity of dynamic coupling between atmospheric, wave, surge, and hydrological model is recognized; therefore, a tremendous effort across modeling groups is in place (Moghimi et al 2020;Bakhtyar et al 2020), leading to improvement in the accuracy of each individual model in the coupled system. On the other hand, the observations including stationary observations, along satellite tracks or radar field snapshots carry errors and uncertainties, mostly due to device accuracy, calibration, and post-processing algorithm.…”
Section: Model and Observation Sources Of Errormentioning
confidence: 99%
“…Decoupling of different shallow water processes, where hydrodynamics and ocean waves are modeled stand-alone or in a one-way fashion, introduces error in the models' outputs. Note that the necessity of dynamic coupling between atmospheric, wave, surge, and hydrological model is recognized; therefore, a tremendous effort across modeling groups is in place (Moghimi et al 2020;Bakhtyar et al 2020), leading to improvement in the accuracy of each individual model in the coupled system. On the other hand, the observations including stationary observations, along satellite tracks or radar field snapshots carry errors and uncertainties, mostly due to device accuracy, calibration, and post-processing algorithm.…”
Section: Model and Observation Sources Of Errormentioning
confidence: 99%
“…Therefore, the downstream boundary conditions are set to be the measured tidal data for all the cases. These effects are incorporated to the present model following the approach of by Brunner (2016b), JAICA (2009), and Bakhtyar et al (2020).…”
Section: Hydrodynamic Modelmentioning
confidence: 99%
“…Additionally, the present modelling approach takes into account the tidal effects at the sea outfall where the sea outfall is set as one of the boundaries with the stage computed using Admiralty tide tables (UKHO 2004) and an external model following the approach of JAICA ( 2009) and Bakhtyar et al (2020). As Kelani River is a tidally influenced river, Gunathilaka et al (2010) showed that the high tide during flood events would create the worst-case scenario in the vicinity of Nagalagam Street.…”
Section: Calibration Of Hydrodynamic Modelmentioning
confidence: 99%
“…It was found that the inclusion of riverine discharge into the SCHSIM model resulted in elevated water surface levels for more than 2 weeks after Hurricane Irene hit that area. Bakhtyar et al (2020b) executed a loose one-way coupling between the NWM and ADCIRC/WAVEWATCH III using the D-Flow FM hydraulic model to assess compound flooding impacts for tropical cyclones in the Delaware river basin and it was shown that water level predictions depend on a detailed representation of riverine discharge and elevated sea levels as well as detailed pressure and wind forcing (Bakhtyar et al, 2020b). Gori et al (2020) investigated the contribution of flooding due to river discharge along the North Carolina coast by loosely coupling the storm surge model ADCIRC, and the hydraulic model HEC-RAS by using ADCIRC output as downstream boundary conditions into the 1-D/2-D HEC-RAS hydraulic model in order to account for the effects of storm surge (Gori et al, 2020).…”
Section: Introductionmentioning
confidence: 99%